Faktor yang Berhubungan dengan Keluhan Musculoskeletal Disorders (MSDs) pada Pekerja Manual Handling: Literatur Review - Firmita Dwiseli; Asterlita Ryane Wenas (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Musculoskeletal Disorders (MSDs) encompassing conditions affecting muscles, bones, joints, ligaments, nerves, and tendons , are a prevalent occupational health issue, particularly in roles involving physical tasks like lifting, pushing, pulling, or carrying loads. This study aims to synthesize current scientific findings on the prevalence, contributing risk factors, and effective prevention strategies for MSDs in manual handling contexts. A systematic literature search was conducted using Google Scholar, focusing on peer-reviewed journal articles published between January 2020 and June 2025. The review identified a consistently high prevalence of MSDs, with the lower back, shoulders, neck, and upper extremities being the most commonly affected areas. Key risk factors are multifactorial, including physical/ergonomic aspects (e.g., awkward postures, heavy loads, repetitive motions, prolonged exposure, vibration) , individual factors (e.g., age, BMI, injury history) , psychosocial factors (e.g., high job demands, low job control, stress) , and organizational/manegerial factors (e.g., inadequate training, poor workstation design). The findings underscore the necessity of a holistic and integrated approach to manage MSDs.